Dopamine Modulates Excitatory Synaptic Transmission by Activating Presynaptic D1-like Dopamine Receptors in the RA Projection Neurons of Zebra Finches - Wang, Songhua; Liu, Shaoyi; Wang, Qingqin; Sun, Yalun; Yao, Lihua; Li, Dongfeng; Meng, Wei (Frontiers in Cellular Neuroscience, 2020)
Songbirds are useful vertebrate study models for vocal learning and memory. The robust nucleus of the arcopallium (RA) receives synaptic inputs from both the posterior and anterior pathways of the song control system in songbirds. Hence, RA plays an important role in the control of singing. RA receives dopaminergic (DArgic) inputs that increase the excitability of RA projection neurons. However, the effects of DA on excitatory synaptic transmission are yet to be deciphered. In this study, the effects of DA on the excitatory synaptic transmission of the projection neurons in the RA of adult male zebra finches were investigated using whole-cell patch-clamp recording. We observed that DA decreased the frequency of spontaneous excitatory postsynaptic currents (sEPSCs) and miniature excitatory postsynaptic currents (mEPSCs). The effects of DA were mimicked by the D1-like DA receptor (D1R) agonist, SKF-38393, but not the D2-like DA receptor (D2R) agonist, Quinpirole. In addition, the effects of DA were blocked by D1R antagonist, SCH-23390, but not the D2R antagonist, Sulpiride. These results demonstrate that DA modulates excitatory synaptic transmission by acting on D1R in the RA of adult male zebra finches.